2021
DOI: 10.1038/s41420-021-00470-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive role of mitochondrial sirtuin 4 in induction of G2/M cell cycle arrest and apoptosis in hepatitis B virus-related hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is developed from uncontrolled cell growth after the malignant transformation of hepatocytes. The hepatitis B virus (HBV) X protein (HBx) has shown to induce cell cycle progression and hepatocarcinogenesis. A sub-fraction of HBx is localized in the mitochondria. Sirtuin 4 (SIRT4), a mitochondrial protein, has been demonstrated to play a tumor-suppressive role in many cancers, including HCC. However, little is known about the association between mitochondrial HBx and SIRT4 during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Similarly, a study has demonstrated that HBV X protein induces cell cycle progression ( 38 ). Sirtuin 4 (SIRT4) suppresses CyclinB1/Cdc2 in HCC, and the expression levels of SIRT4 in HBV-infected patients are lower than those in uninfected patients ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a study has demonstrated that HBV X protein induces cell cycle progression ( 38 ). Sirtuin 4 (SIRT4) suppresses CyclinB1/Cdc2 in HCC, and the expression levels of SIRT4 in HBV-infected patients are lower than those in uninfected patients ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study revealed that DHA had no significant effect on the protein expression levels of CCNB1 in HepG2 cells. This result may be due to the fact that the integration of hepatitis B virus (HBV) induced CCNB1 expression in HepG2215 cells compared with HepG2 cells ( 38 ). Similarly, a study has demonstrated that HBV X protein induces cell cycle progression ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, current evidence shows that the expression of all SIRT proteins can be modulated by HBV. In particular, expression levels of SIRT1 (6), SIRT2 (7), SIRT5 (8), and SIRT7 were found to be increased in HBV-infected cells (8,9), whereas those of SIRT3, SIRT4, and SIRT6 were decreased in HBV-infected hepatocytes (10)(11)(12)21). Of note, studies have also demonstrated that changes in the expression level of SIRT1 (14), SIRT2 (7), SIRT3 (11), SIRT4 (10), and SIRT7 are associated with a nonstructural viral protein, HBx (9).…”
Section: Effect Of Hbv On Sirtsmentioning
confidence: 99%
“…Sirtuins (SIRTs) are nicotinamide adenine dinucleotide (NAD) + -dependent histone deacetylases that regulate various biological processes, including stress responses, apoptosis, and metabolism (4,5). In particular, emerging evidence shows that SIRTs play a significant role in chronic HBV infection (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%